Review and comparative analysis of potent individual dosimetric monitoring systems for Ukrainian NPPs - V. V. Chumak; V. M. Volosky (Ядерна фізика та енергетика)
Individual dosimetric monitoring (IDM) of external exposure of the personnel of nuclear power facilities is a key element of the radiation protection system, is traditionally within the responsibility of NPP radiation safety shops and is carried out by appropriately equipped IDM laboratories. The equipment of the IDM at NPPs, which was commissioned in the mid-2000's, is coming to the end of its life cycle and the issue of equipment replacement is on the agenda now. New IDM systems that will operate for the next 10 - 15 years should meet modern requirements, take into account global trends in radiological protection and the latest developments of IDM instrumentation, while the choice of new systems should be based on international and domestic experience, adequacy of dosimetric performance and operational practicality. The review is devoted to the comparison of the characteristics of the potent passive personal dosimetry systems considered for IDM of Ukrainian NPP personnel. Based on the analysis of literature data, international standards and recommendations, information from manufacturers and authors’ own practical experience, a generalization of information on existing and future IDM systems is carried out, a vision of the most optimal choice of systems for re-equipping laboratories for dosimetric monitoring of nuclear power plants good for the next decade is proposed.